Constitutional measurements of public interest, protected in the performance of executive activity - Nikolova, Raina (Law Journal of New Bulgarian University, 2021)
The public interest in carrying out enforcement activities in a constitutional sense is to provide guarantees for compliance with the fundamental principles. In order to exercise the fundamental rights of citizens in the performance of their enforcement activities, the common interest can be formulated by imposing restrictions on them.